National development via National service training program : RA 9163 common modules for CWTS, LTS and ROTC - Dela Cruz, Sonia Gasilla; Dela Cruz, Edeliza ;Mapue, Paul (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2019)
The program aims to strengthen the students active participation in the program and activities intended to uplift the different dimensions of community development.
Module 1. NSTP Program (RA 9163) -- Module 2. Citizenship Training -- Module 3. NSTP Program (RA 9163) -- Module 4. NSTP Program (RA 9163) -- Module 5. Disaster Risk Reduction and management awareness -- Module 6. Environmental Protection -- Module 7. Other National Security -- References..
Includes bibliographical references.
Keywords: NATIONAL SERVICE -- PHILIPPINES